INTERCONNECTIONSBETWEEN OF COMPONENTS OFTECHNOLOGICAL INTERACTION OFINDUSTRIAL ROBOTS’ GRIPPERSWITH AN OBJECTSOFMANIPYLATION - Kyrylovych, V. (Energy and Automation, 2016)
The structure and content of technological interaction (TI) of industrial robots’ grippers and objects of manipulation as one of the components of a system a tic approach to automated synthesis of robotic mechanical assembly technologies are reviewed. The essence of vector-projective, geometrically-power and trajectory-dynamic tasks of TI are described. There are graphically illustrated he complex of causal relationship between the components of TI. The content and sequence of automated calculation of formalize are presented constituents of TI are represented. The content and the sequence of automated calculation of TI are presented in the form of developed formalisms that there are the interconnections between of components of TI of industrial robots’ grippers with an objects of manipulation.